2003
DOI: 10.1007/s00122-002-1123-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of isothiocyanate-enriched broccoli, and its enhanced ability to induce phase 2 detoxification enzymes in mammalian cells

Abstract: Broccoli florets contain low levels of 3-methylsuphinylpropyl and 4-methylsulphinylbutyl glucosinolates. Following tissue disruption, these glucosinolates are hydrolysed to the corresponding isothiocyanates (ITCs), which have been associated with anticarcinogenic activity through a number of physiological mechanisms including the induction of phase II detoxification enzymes and apoptosis. In this paper, we describe the development of ITC-enriched broccoli through the introgression of three small segments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
155
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(162 citation statements)
references
References 28 publications
6
155
0
1
Order By: Relevance
“…The underlying genes are likely to correspond directly to cloned genes that have been functionally analysed in Arabidopsis, described above. In addition, quantitative trait loci (QTLs) have been identified that determine the overall level of GLSs in both B. napus [59,60] and B. oleracea [61,62]. The genetic regulation of indolyl glucoisnolates derived from tryptophan is far less advanced.…”
Section: Breeding For Altered Gls Content In Brassicamentioning
confidence: 99%
“…The underlying genes are likely to correspond directly to cloned genes that have been functionally analysed in Arabidopsis, described above. In addition, quantitative trait loci (QTLs) have been identified that determine the overall level of GLSs in both B. napus [59,60] and B. oleracea [61,62]. The genetic regulation of indolyl glucoisnolates derived from tryptophan is far less advanced.…”
Section: Breeding For Altered Gls Content In Brassicamentioning
confidence: 99%
“…In addition to determining the ratio of 3C to 4C chain lengths, the Gsl-elong locus functions as a quantitative trait locus determining overall levels of Metderived GSLs (de Quiros et al, 2000;Kroymann et al, 2001), similar to a quantitative trait locus in Brassica that determines both 3C to 4C ratio and total amounts (Mithen et al, 2003). Fine mapping and sequence analysis in several Arabidopsis ecotypes reveal that the Gsl-elong locus comprises, in addition to MAM1 and MAML, a further gene designated MAM2.…”
mentioning
confidence: 99%
“…Breeding approaches have been used to increase levels of flavonoids in onion and carotenes and anthocyanins in carrot [33,80,119]. Although precise comparisons between wild and cultivated broccoli species is complicated by differences in floret morphology some authors have estimated that florets of cultivated broccoli lines contain 3 -10 tmol g -1 DW of glucosinolates whilst wild species contain between 50 -100 tmol g -1 DW glucosinolates [110]. The development of hybrid broccoli varieties with higher levels of glucoraphanin, the precursor of the anticarcinogenic isothiocyanate sulforaphane, by introgression of the wild broccoli ancestor Brassica villosa has been described [47,110,152].…”
Section: Plant Breeding For Bio-fortified Cropsmentioning
confidence: 99%
“…Although precise comparisons between wild and cultivated broccoli species is complicated by differences in floret morphology some authors have estimated that florets of cultivated broccoli lines contain 3 -10 tmol g -1 DW of glucosinolates whilst wild species contain between 50 -100 tmol g -1 DW glucosinolates [110]. The development of hybrid broccoli varieties with higher levels of glucoraphanin, the precursor of the anticarcinogenic isothiocyanate sulforaphane, by introgression of the wild broccoli ancestor Brassica villosa has been described [47,110,152]. Hybrid broccoli lines have been licensed to a commercial company for commercialisation, which is expected to occur in the next couple of years (R.Mithen personal communication).…”
Section: Plant Breeding For Bio-fortified Cropsmentioning
confidence: 99%